Die Funktionen anaphorischer Proformen beim Simultandolmetschen aus dem Deutschen - Dubslaff, Friedel (HERMES - Journal of Language and Communication in Business, 1993)
When working from German in the simultaneous mode, interpreters often start producing the target language utterance before they have heard the end of the source language utterance in question. The reason for this is that the short-term memory may become overloaded if the interpreter decides to wait for the whole utterance to be complete. As soon as he has captured the full meaning of the German utterance (or a meaning unit of it) he will take the incomplete output segment up again by means of anaphoric pro-forms (such as resumptive pronouns), correct it, if necessary, and/or complete it in accordance with the requirements of his target language production. This paper shows that, as they may be used for various functions in the process, anaphoric pro-forms are a flexible processing device.